MOTIVASI ANGGOTA KELOMPOK WANITA TANI DALAM DIVERSIFIKASI PANGAN LOKAL DI KABUPATEN BANTUL - Resti Kinasih; Subejo Subejo; Roso Witjaksono (Agro Ekonomi, 2014)
This research was done in Bantul district. The purposes of this research were to find out the motivation rate of women farmers group in diversification of local food in Bantul district, the influencing factors, and also to find out the influence of motivation and the other factors to successing local food diversification. This research bassicaly applied analytic descriptive method and used purposive method for sub-district and women farmers group sampling. It was took 15 group members from each women farmers group using simple random sampling, so in total there were 60 members as sample. Data analysis has been done by using propostion test and multiple regression analysis. The research results showed that the larger part of women farmers group in Bantul district have a high motivation on the local food diversification, price of rice and active counseling have a possitive influence on motivation. Meanwhile, age, level of education, income, perception of local foods, and mass media access do not have influence to the motivation of local food diversivication. Price of rice has a negative influence on success local food diversification, while income, active counseling, perception of local foods have a possitive influence of local food diversification sucess. Meanwhile, age, level of education, mass media access and motivation do not have influence on local food diversification success.